Probabilistic Resource Assessment of The Ulumbu Geothermal Field, East Nusa Tenggara, Indonesia - Heru Berian Pratama; Iqbal Kurniawan; Sutopo Sutopo (Indonesian Journal on Geoscience, 2022)
DOI:10.17014/ijog.9.2.183-193A resource assessment of the Ulumbu Geothermal Field, East Nusa Tenggara, Indonesia, is proposed here. The fundamental issue of reserve estimation is determining the optimum capacity to be installed (field size) that affects the decision-making in geothermal projects. The reservoir numerical model and heat stored method are the most appropriate tools for geothermal resource assessment. Therefore, the hybrid numerical simulation and heat stored methods, coupled with the probabilistic approach, are applied to Ulumbu. Based on the calibrated numerical model, the estimation of the reservoir is divided into the steam zone and liquid reservoir. The energy reserve of the Ulumbu is estimated by Monte Carlo simulation with the results P10-P50-P90 are 71 MWe, 95 MWe, and 127 MWe, respectively